Physical Activity and Sitting Time Patterns and Sociodemographic Correlates Among 155,790 South American Adults - De Moraes-Ferrari, G (Human Kinetics Publishers Inc., 2023)
Background: To estimate the prevalence of different physical activity (PA) domains and sitting time (ST), and to analyze the association with sociodemographic indicators. Methods: Data from the most recent nationally representative survey from each of the South American countries, comprising 155,790 adults (18–64 y), were used. Data on leisure-time, transport, and occupational PA (all 3 domains as nonzero), total PA (≥150 min/wk), and ST (≥8 h/d) were assessed by specific questionnaires in each survey. Gender, age group (18–34, 35–49, and 50–64 y), and education (quintiles) were used as sociodemographic factors. Random effect meta-analysis of the association between sociodemographic factors and PA and ST were conducted. Results: The prevalence of PA guidelines compliance and elevated ST in South America was 70.3% and 14.1%, respectively. Women were less likely to achieve the recommended levels of total and domain-based PA. Participants in the highest quintile of education were more likely for elevated ST (2.80, 2.08–3.77), lower occupational PA (0.65, 0.44–0.95), but higher leisure-time PA (3.13, 2.31–4.27), in comparison with lowest quintile. Older adults were less likely to participate in total and leisure-time PA. Conclusion: Our findings highlight the urge to tackle the inequalities in PA practice in South America, especially gender and education inequalities, for leisure-time PA. © 2023 Human Kinetics, Inc.